2020
DOI: 10.7812/tpp/20.028
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Burnout: A Pilot Study of International Women Physicians

Abstract: In the heart of New York City, adjacent to the Chrysler Building (left), the famed architect Philip Johnson designed the Trylons "as a monument for 42nd Street… to give you the top of the Chrysler building at street level" via visual analogy with the chevron-ornamented spire of its namesake. It's one of many visual reminders that the epicenter of the COVID-19 pandemic in the US is still a bejeweled city.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…A very small percentage of HCPs presented high/severe burnout in all three subscales, results that do not match other studies indicating a BS prevalence of up to 55% among HCPs during the COVID-19 pandemic 18 . However, the low rate of Clientrelated Burnout matches other international studies using the CBI 33 . It also seems that being a physician, years of work, and working in the public sector, result in higher levels of Burnout, contrasting with studies arguing that BS is correlated with gender and marital status 7 but agreeing with the results of Αfonso et al 7 who found that workplace rather than personal factors weighs more heavily in the occurrence of BS.…”
Section: Discussionsupporting
confidence: 82%
“…A very small percentage of HCPs presented high/severe burnout in all three subscales, results that do not match other studies indicating a BS prevalence of up to 55% among HCPs during the COVID-19 pandemic 18 . However, the low rate of Clientrelated Burnout matches other international studies using the CBI 33 . It also seems that being a physician, years of work, and working in the public sector, result in higher levels of Burnout, contrasting with studies arguing that BS is correlated with gender and marital status 7 but agreeing with the results of Αfonso et al 7 who found that workplace rather than personal factors weighs more heavily in the occurrence of BS.…”
Section: Discussionsupporting
confidence: 82%
“…Some of these factors include women physician wellness, resiliency, and risks of burnout. [11][12][13] However, despite these efforts, significant gender disparity in academic EM persists. There also remains a gap in our understanding of the specific drivers of gender disparity in academic EM.…”
Section: Introductionmentioning
confidence: 99%
“…We did not explore possible protective factors against psychological distress and burnout which may have led to an overestimation of distress in our study [42]. This study also did not account for other factors that have been shown to contribute to affect wellbeing among females such as wage disparities, gender bias and discrimination, poor social and organizational support, and microaggressions and harassment [43][44][45]. Future studies should also incorporate negative interactions with patients as possible stress-related factors.…”
Section: Limitationsmentioning
confidence: 99%